Manipulating the Ulva holobiont: Co-culturing Ulva ohnoi with Phaeobacter bacteria as a strategy for disease control in fish-macroalgae IMTA-RAS aquaculture - Pintado, José; Olmo, Gonzalo del; Gulnebert, Thomas; Ruiz García, Patricia; Nappi, Jadranka; Thomas, Torsten; Egan, Suhelen; Masaló, Ingrid; Cremades, Javier (Journal of Applied Phycology, 2023)
13 pages, 6 figures.-- This article is licensed under a Creative Commons Attribution 4.0 International License The green alga Ulva ohnoi M. Hiraoka & S. Shimada is an effective biofiltration agent of fish effluents in Integrated Multi-Trophic Aquaculture Recirculation Systems (IMTA-RAS), due to its high growth rate and high nutrient (N and P) removal in temperate conditions. Moreover, Ulva species provide an important niche for biofilm-forming bacteria, including strains of Phaeobacter that possess antagonistic activity against pathogenic Vibrio species, and have been shown to reduce the mortality of fish in aquaculture settings. This research aimed to examine the potential of using U. ohnoi colonised with Phaeobacter sp. 4UAC3, previously isolated from natural populations of Ulva australis, as a strategy to prevent vibriosis in IMTA-RAS. The results showed that Phaeobacter sp. 4UAC3 was able to colonise and be maintained on U. ohnoi during a re-inoculation scale-up process from multi-well plates (10 mL) to flasks (4 L) and finally to tanks (40 L). Phaeobacter sp. 4UAC3 rapidly colonised the surface of the Ulva but it did not significantly modify the rest of the bacterial communities present in U. ohnoi surface in terms of diversity and composition. Infection assays using fish larvae (Scophthalmus maximus) with V. anguillarum in a model IMTA-RAS showed that Phaeobacter–colonized U. ohnoi promoted the reduction of mortality in the infected larvae, however this trend was not statistically supported. These results suggested that U. ohnoi can be experimentally colonised with Phaeobacter sp. 4UAC3 and has potential to be used in IMTA-RAS as an alternative to traditional disease control methods Open Access funding provided thanks to the CRUE-CSIC agreement with Springer Nature. The IntegRas project (AGL2013-41868-R) and the UlvaQuo Project (RTI2018-095062-B-C21) were funded by the Spanish Agencia Estatal de Investigación. Gonzalo Del Olmo was beneficiary of a grant from the Galician Axencia Galega de ...